2017
DOI: 10.1088/1367-2630/aa6f37
|View full text |Cite
|
Sign up to set email alerts
|

Quantum simulation of the Abelian-Higgs lattice gauge theory with ultracold atoms

Abstract: We present a quantum simulation scheme for the Abelian-Higgs lattice gauge theory using ultracold bosonic atoms in optical lattices. The model contains both gauge and Higgs scalar fields, and exhibits interesting phases related to confinement and the Higgs mechanism. The model can be simulated by an atomic Hamiltonian, by first mapping the local gauge symmetry to an internal symmetry of the atomic system, the conservation of hyperfine angular momentum in atomic collisions. By including auxiliary bosons in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 129 publications
(283 reference statements)
2
47
0
Order By: Relevance
“…The same authors presented in [394] another simulation scheme for SU (2), which avoided the need for decomposing the links by using the invariant truncation scheme introduced in [363]. More recently González-Cuadra et al [411] showed how six bosonic species would be enough to simulate the Abelian-Higgs model (i.e. a scalar field with U (1) gauge symmetry) based on the same angular momentum conserving scheme.…”
Section: Analog Proposals: Different Strategies For Gauge Invariancementioning
confidence: 99%
“…The same authors presented in [394] another simulation scheme for SU (2), which avoided the need for decomposing the links by using the invariant truncation scheme introduced in [363]. More recently González-Cuadra et al [411] showed how six bosonic species would be enough to simulate the Abelian-Higgs model (i.e. a scalar field with U (1) gauge symmetry) based on the same angular momentum conserving scheme.…”
Section: Analog Proposals: Different Strategies For Gauge Invariancementioning
confidence: 99%
“…By inspection of (40) we see that for an upper bound on the digitization error of the standard Trotter formula, the commutators among all different parts of the Hamiltonian in (43) have to be evaluated, as well as their norms Since the derivations are very lengthy we will refer the interested reader to the appendix. We provide here the final result: where d is the number of spatial dimensions, d U the dimension of the representation of the group element operator U and  links the number of links in the lattice.…”
Section: First Order Formulamentioning
confidence: 99%
“…There are also differences in the proposed simulation scheme: the first one is the analogue approach, where not only the degrees of freedom of the simulated system are mapped to those of the simulating one: by appropriately tailoring the interactions of the simulator, its Hamiltonian is exactly or approximately mapped to the desired one (which can be adiabatically changed). Quantum simulations of this type have been proposed, mostly using ultracold atoms [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44], as well as trapped ions [45,46] and superconducting qubits [47,48]. Another approach-the digital one-is based on an idea of Feynman [49], to use a quantum computer (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…With the help of projectors (16)- (19) and identities (20), we rewrite the block matrix h in terms of spin and pseudospin operators as follows…”
Section: Basis Statesmentioning
confidence: 99%
“…Experimental research of ultracold atoms in optical lattices have dramatically expanded the possibilities of a tunable simulation in quantum many-body physics [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Moreover, ultracold atoms open the path to the parameter range that is hardly possible or even impossible to achieve in the natural condensed matter systems [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%